Measurement of stopping power of alpha particles in light matter - le, Chung Xuan; Ha, Hoa Thi Mai; Pham, Hung Quoc; Duong, Tung Thanh; Doan, Tuyen Quang (VNU Journal of Science: Mathematics - Physics, 2017)
Abstracts